Affective-Sexual Health Promotion in Early Childhood: Critical Review in The Context of Childcare and Education in Costa Rica - Milvia Rodríguez Sánchez; Laura Brenes Vásquez (Revista Costarricense de Psicología, 2023)
This critical review describes research on affective and sexual development in early childhood in preschool and childcare settings. Studies are analyzed from the point of view of the regulatory and operational frameworks on which education on this topic in Costa Rica is based. The review was carried out using 4 international databases, examining empirical studies and review studies. Costa Rica has put in place a broad national-level policy framework that supports a comprehensive understanding of affective-sexual  development from infancy. However, implementation of the policy in the national preschool program does not always meet the framework’s standards. We find that the risk of sexual abuse tends to be prioritized in early sexual-affective education. Sexual-affective development is often addressed from a moralistic standpoint, advising for instance that the genitals should be named only  in the last levels of preschool and not when the other parts of the body are first named. From a health-promotional perspective on  national childcare and early education, we here propose a broader view that takes fully into account the complexities around the  social determinants of sexual-affective development. We conclude that an update of the preschool program is required,  accompanied by continuous training for staff and families of infants.